Effect of Micro- and Nano-Sized Carbonous Solid Lubricants as Oil Additives in Nanofluid on Tribological Properties - Emad Omrani; Pradeep L. Menezes; Pradeep K. Rohatgi (Lubricants, 2019)
The tribological behavior of graphene and graphite as additives in canola oil was investigated with a pin-on-disk tribometer. The wear surfaces of the aluminum pins lubricated with the additive-containing canola oil were analyzed by scanning electron microscopy (SEM). It was found that graphene and graphite as additives in oil show a lower coefficient of friction and wear rate in comparison with neat canola oil. The graphene sheets are more effective than graphite flakes to reduce friction and wear. In addition, there is a proper concentration where the coefficient of friction (COF) and wear are in minimum value. The optimal concentration of the additive in canola oil is about 0.7 wt %. Therefore, the load-carrying capacity and antiwear ability of the lubricating oil are improved. Moreover, the worn surface of aluminum pins is smother in the presence of solid lubricant rather than neat oil.